A review of intra-Philippine distribution patterns of Philippine mosses based on recent evidence of tectonic evolution of the archipelago insights and problems - Linis, Virgilio C. (2006)
A recent review of the distribution patterns of Philippine mosses is presented. Interpretation about the distribution of local moss flora through correlation with information from the latest plate tectonic history of the archipelago, which has its beginning from the Oligocene period, is discussed. Long distance and chance dispersal as alternative explanations for local moss distribution are also supported.
Keywords: Philippine Mosses; Moss flora